Colorectal cancer - Progress rehabilitation after surgery - Agnieszka Filarecka; Maciej Biernacki; Paweł Kaźimierczak; Rafał Kaźimierczak (Kazimierz Wielki University, 2019)
When colorectal cancer is removed, either by laparoscopic or classical open method, traumatization of the abdominal tissues occurs. Damage in the form of cutting muscle fibers is associated with a disorder of postural muscle tone. A scar itself within the abdominal cavity can create mobility restrictions in the form of restrictions on the mobility of the spine. The implementation of rehabilitation before and after surgery should be an indispensable element in the treatment of colorectal cancer. The work aims to present therapy proposals using modern special rehabilitation methods to improve patients after surgical treatment of colorectal cancer. The paper presents examples of activities that can be used in therapy in its various phases. A review of available literature and own experience were used for the work. From the analyzed literature, it can be concluded that rehabilitation of oncological patients is not widespread and often overlooked in the treatment process. Patients often after surgery to remove colorectal cancer are not subject to rehabilitation, pre-operative rehabilitation also occurs sporadically according to literature. Rehabilitation of patients after surgical treatment of colorectal cancer should take place before and after surgery. Rehabilitation should take into account the weakening of the muscle strength in the torso and mobility limitations caused by the postoperative scar. Rehabilitation should be aimed at restoring functionality.